LITERATUR REVIEW: TINJAUAN TENTANG EFEKTIFITAS TERAPI NON FARMAKOLOGI TERHADAP PENURUNAN INTENSITAS NYERI PERSALINAN KALA I - Hasnah, Hasnah; Kb, Muhammad Allfian Rajab; Muaningsih, Muaningsih (Universitas Islam Negeri Alauddin Makassar, 2018)
Labor pain is a physiological condition. Pain originates from uterine contractions and cervical dilatation. With increasing volume and frequency of uterine contractions, the pain that is felt will be stronger, the peak of pain occurs in the active phase, where the complete opening is up to 10 cm and lasts around 4.6 hours for primiparas and 2.4 hours for multiparas. Handling pain in childbirth is the main thing that must be considered by health care providers when giving birth assistance. Therefore it is important to treat pain for the mother during labor. This review literature aims to find out non-pharmacological therapies that are effective in reducing pain at first stage of labor, so that it can be used as an alternative method of handling pain in labor. Method: This review literature is done by searching articles using electronic databases, namely google schoolar. Keywords used